Evaluating California's Sustainable Groundwater Management Act: The First Five Years of Governance and Planning. (1st November 2021) - Leach, William D.; An, Brian Y.; Tang, Shui‐Yan
Abstract: California's landmark 2014 Sustainable Groundwater Management Act (SGMA) requires local officials to form new Groundwater Sustainability Agencies (GSAs) and to write new groundwater sustainability plans capable of eliminating overdraft within 20 years. To assess progress achieved during SGMA's first five years of implementation, we surveyed officials who manage or participate in GSA governance. The most common obstacles to GSA formation have involved horizontal and network governance issues such as too many diverse interests or lack of trust among stakeholders. The most common obstacles to groundwater planning include a lack of financial resources and the requirement to coordinate plans among GSAs in the same basin. Respondents usually report that their own GSA performs well on seven measures of good governance, such as representing all major stakeholders, granting members sufficient power, and generating trusted data for decision making. On the other hand, many GSA managers acknowledge that some types of stakeholders remain underrepresented in the governing structure despite SGMA's mandate to "consider the interests of all beneficial uses and users of groundwater." Overall, most respondents are optimistic that SGMA will enhance groundwater sustainability locally and statewide. If successfully implemented and fully funded, SGMA could become a model worldwide for sustainable resource governance that combines top‐down mandates and local incentives.